Effect of thermo-sonication condition on carotenoid yield and its antioxidant activity - Lasunon, Patareeya; Phonkerd, Nutchanat; Tettawong, Prapaporn; Sengkhamparn, Nipaporn (Asia-Pacific Journal of Science and Technology, 2022)
The carotenoids can be extracted from many plants by using many techniques in order to obtain the highest yield. However, the extraction condition also be affected to the quality of the extracts. This work aimed to study the effect of thermo sonication on carotenoid yield as well as its antioxidation activity. The Fuzzy analytical method was used to be applied to gain the best condition which gave both the quantity and quality. The carotenoids were extracted from industrial tomato waste using a thermo-sonication method at different conditions namely extraction temperatures of 30, 50, or 70 °C and extraction times of 10, 30, or 50 min. The High Performance Liquid Chromatograph (HPLC) chromatogram showed that the crude extract was composed of trans-lycopene as well as β-carotene. The extraction temperature of 50 °C gave the highest carotenoid content, while extraction times of 30 and 50 min were comparable. The antioxidant activity of crude extract was determined using 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activity and Inhibition of lipid peroxidation. Nevertheless, the antioxidant activities of the extract were not in agreement with a carotenoid yield which extracted at 30 and 70 °C gave a higher level than that at 50 °C. The performance index was calculated by triangular fuzzy analytical method using 4 criteria, which were trans-lycopene and β-carotene content, as well as the 2 measurements of antioxidant activity, with the weight of 30:20:25:25, respectively. The extraction condition that yielded the highest performance index was the extraction temperature of 70 °C for 10 min.